2007
DOI: 10.1080/02640410701287131
|View full text |Cite
|
Sign up to set email alerts
|

Body mass changes and nutrient intake of dinghy sailors while racing

Abstract: Dinghy sailing is a physically challenging sport with competitors on water for several hours. Regulations and space in the boat limit the amount of food and fluid competitors can carry. Consequently, it is possible that the hydration and nutritional status of dinghy sailors may be compromised while racing. Despite this, the food and fluid intake of sailors while racing are unknown. The aim of this study was to assess the dietary intake of a group of club sailors while racing and compare this with current sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
1
21
1
2
Order By: Relevance
“…The athletes are regularly far away from the coast, and they wear sailing suits made of neoprene and latex materials that do not allow regular perspiration. It has already been noted that most of the sailing athletes are in a negative fluid balance after racing (mean loss for males: - 2.1%; for females: - 0.9%) [14]. In addition, Croatia is a Mediterranean country with a temperature ranging from 15 to 30 degrees Celsius (from March through the end of September, when most sailing occurs), and it is clear that adequate rehydration is difficult to achieve without isotonic drinks.…”
Section: Discussionmentioning
confidence: 99%
“…The athletes are regularly far away from the coast, and they wear sailing suits made of neoprene and latex materials that do not allow regular perspiration. It has already been noted that most of the sailing athletes are in a negative fluid balance after racing (mean loss for males: - 2.1%; for females: - 0.9%) [14]. In addition, Croatia is a Mediterranean country with a temperature ranging from 15 to 30 degrees Celsius (from March through the end of September, when most sailing occurs), and it is clear that adequate rehydration is difficult to achieve without isotonic drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Only two previous studies have directly recorded hydration status in competitive sailors. Slater and Tan reported dehydration greater than 2% of body weight in sailors, potentially leading to performance decrements (Slater & Tan, 2007). Lewis et al reported significant body mass losses in competitive sailors even in cold conditions despite ad libitum fluid intake (Lewis, Fraser, Thomas, & Wells, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, athletes remain on the water for long durations with limited access to fluids due to the nature of the sport and lack of space in the boat (Allen & De Jong, 2006). The small amount of research specific to sailing performance and nutrition indicates that sailors fail to prevent dehydration greater than -2% of body weight throughout competition (Slater & Tan, 2007). Also, elite sailors demonstrate a lack of knowledge regarding sports nutrition, including guidelines for fluid consumption during exercise (Legg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos apontam as diversas exigências necessárias para a prática da vela, como: demandas de força, equilíbrio, coordenação, resistência, nutrição adequada, além de boas condições psicológicas para interpretar adequadamente ações do vento e do mar, tomar decisões rápidas, e manter a concentração e o foco de atenção (SLATER; TAN, 2007;DUARTE, 2007;MACKIE;LEGG, 1999;DAUTY et al, 2006;BERNARDI et al, 2007;CUNNINGHAM;HALE, 2007;LÉGER et al, 2007;PARDAL;SPURWAY, 2007;VALLEJO;ROSIQUE;GONZÁLEZ-MORO, 2008). Somado a isso, também se torna necessária uma boa atenção em tarefas individuais e simultâneas, estando estas relacionadas à capacidade do velejador em automatizar tarefas (ABERNETHY et al, 2007).…”
Section: Característica E Demandas Relacionadas à Velaunclassified
“…A prática da vela consiste em uma atividade esportiva que, devido às suas complexas características, exige fisicamente do atleta e o estimula intelectualmente (SLATER; TAN, 2007). Um barco a vela sempre navega movimentado pelo vento, pois não é permitido o uso de motores ou outros meios de propulsão durante as regatas (MAIA, 2008).…”
Section: Introductionunclassified